2016
DOI: 10.1002/mds.26573
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-hydroxyvitamin D concentrations in Mid-adulthood and Parkinson's disease risk

Abstract: Background Low vitamin D levels are common among patients with Parkinson’s disease (PD). Experimental evidence further suggests that vitamin D may be protective against PD. Objectives We prospectively assessed the association between serum 25-hydroxyvitamin D and PD among 12,762 participants of the Atherosclerosis Risk in Communities Study cohort. Methods Serum samples were collected in 1990–1992 and 25-hydroxyvitamin D was measured by liquid chromatography mass spectrometry. A total of 67 incident PD case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…These results were in accordance with the view that MSA share neuropathogeneses similarities with PD. Our data further suggest that Klt and 25(OH)D may act as a neuroprotective role in MSA and PD via attenuating inflammation . Therefore, in the assessment and diagnosis of MSA/PD, klt and 25(OH)D were found to be suitable in this study.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…These results were in accordance with the view that MSA share neuropathogeneses similarities with PD. Our data further suggest that Klt and 25(OH)D may act as a neuroprotective role in MSA and PD via attenuating inflammation . Therefore, in the assessment and diagnosis of MSA/PD, klt and 25(OH)D were found to be suitable in this study.…”
Section: Discussionmentioning
confidence: 55%
“…Significantly lower plasma Klt levels in MSA/PD patients implied that Klt may attribute to the pathogenesis of the disease . Recently, 25(OH)D has gained much attention due to its crucial role in the pathological mechanism of PD . Other reports have revealed that 25(OH)D deficiency may lead to a high risk of developing MS .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a published vitamin D intervention study has demonstrated positive effects of vitamin D supplementation on clinical rating scales in PD patients (Suzuki et al, 2013), providing clinical evidence for a potential therapeutic role for vitamin D or calcitriol. However, not all studies have found an association between vitamin D levels and PD (Petersen et al, 2014; Shrestha et al, 2016). Thus, the link between low levels of vitamin D and PD is controversial, and may only apply to some individuals with PD.…”
Section: Discussionmentioning
confidence: 98%
“…Complications exist, however. For example, the first epidemiological risk study from Finland found lower baseline vitamin D levels in individuals who went on to develop PD compared to those who did not, but the more recent prospective Atherosclerosis Risk in Communities (ARIC) study cohort of almost 13,000 subjects found no association between baseline vitamin D levels and risk of PD 17 years later . Moreover, whereas studies involving populations with more advanced PD have consistently shown associations between decreased vitamin D and PD, they face potential confounding attributed to reduced sun exposure, leading to reduced dermal synthesis of Vitamin D, in patients with progressive motor limitations.…”
mentioning
confidence: 99%